Ecopedagogy – Dehumanisation or Humanisation: P. Freire and Z. Bauman - Tuleikytė, Julija (Acta Paedagogica Vilnensia, 2022)
This paper analyzes whether Paulo Freire’s critical pedagogy, which Freire defines as humanization, can be ecopedagogy, and if ecopedagogy is humanization. The text addresses the question of the actuality of Freire’s critical pedagogy and inquires whether it responds to such contemporary questions as the relation between the human being and the planet, or whether it, in a modern manner, prioritizes free human agency before the environment. As an instrument, a comparison is used of Paulo Freire’s and Zygmunt Bauman’s conceptions of phenomena encompassed by dehumanization and humanization. After an analysis of the social critique suggested by the thinkers in the aspect of dehumanization, a conclusion is made that ecopedagogy is humanization in the Freirean critical pedagogy sense, and Bauman’s social conception can serve as an example for a contemporary re-inventing of Freire’s critical pedagogy.